The Effectiveness of Quizwhizzer on Students’ Past Tense Mastery - Muhammad Risnanda Imawan; Muh Shofiyuddin (Universitas Pahlawan Tuanku Tambusai, 2026)
English is crucial for students as it serves as the global language of communication, education, and technology, opening doors to higher education, international career opportunities, and access to fast information resources. Many students struggle to understand grammatical, particularly past tense, due to the repetitive teaching methods and low engagement that negatively impact their learning outcomes in English. This study was conducted to examine whether the Quiz Whizzer application media has a positive influence on students’ learning. The study was conducted on tenth-grade students’ using a quantitative research method. Quantitative data were obtained from pre-test and post-test result. The findings indicate an increase in students’ learning outcomes in the past tense material, with the experimental class achieving an average score of 84.88 and the control class 81.61. therefore, it can be concluded that Quiz Whizzer is effectively used to improve students’ learning outcomes.